Detection of bla SHV and bla CTX-M genes in ESBL producing Klebsiella pneumoniae isolated from Egyptian patients with suspected nosocomial infections - Ahmed, Ola Ibrahim; El-Hady, Soha A.; Ahmed, Tamer M.; Ahmed, Iman Z. (The Egyptian journal of medical human genetics, 2013)
The correct identification of the genes involved in ESBL mediated resistance is necessary for the surveillance and epidemiological studies of their transmission in hospitals. The aim of the present study was to find the prevalence of ESBL producing Klebsiella pneumoniae among K. pneumoniae isolates separated from Egyptian patients with suspected nosocomial infections, to detect their drug resistance pattern and to look for bla SHV and bla CTX-M genes in such organisms. Subjects and methods: 138 K. pneumoniae isolates from Egyptian patients with suspected nosocomial infections were screened for ESBL production by the pattern of antimicrobial susceptibilities. Phenotypic identification for ESBL production was confirmed by double disc synergy test, phenotypic confirmatory double disc test and by MicroScan panel system. bla SHV and bla CTX-M genes in ESBL producing K. pneumoniae were detected using multiplex PCR. Results: The prevalence of ESBL producing K. pneumoniae was 21% (30/138). Their pattern of antimicrobial susceptibility showed that 90% was resistant to (Sulphamethoxazole/Trimethoprim), 70% was resistant to (Amoxicillin/Clavulanate), 63.3% was resistant to Cefotaxime and Ceftazidime, 60% was resistant to Amikacin, 46.7% was resistant to Doxycycline, Cefoxitin, Ceftriaxone and Levofloxacin, 40% was resistant to Cefepime, 20% was resistant to Ertapenem and (Sulbactam/Cefoperazone), 13.3% was resistant to (Piperacillin/Tazobactam), 10% was resistant to (Imipenem/Cilastatin) and Gentamycin and 6.7% was resistant to Meropenem and Ciprofloxacin. Among the ESBL producing K. pneumoniae, three out of 30 (10%) and 16 out of 30 (53.3%) were positive for bla SHV and bla CTX-M genes respectively. It could be concluded that ESBL producing isolates of K. pneumoniae have been increasingly recognized in the hospital settings in Egypt and are associated with multiple drug resistance. Thus, molecular identification of the genes encoding beta lactamases would be essential for a reliable epidemiological investigation of their transmission in hospitals and antimicrobial resistance.